Esophageal atresia and tracheoesophageal fistula: prenatal sonographic manifestation from early to late pregnancy. (1st July 2021) - Kassif, E.; Weissbach, T.; Kushnir, A.; Shust‐Barequet, S.; Elkan‐Miller, T.; Mazkereth, R.; Weissmann‐Brenner, A.; Achiron, R.; Weisz, B.
ABSTRACT: Objective: Esophageal atresia and/or tracheoesophageal fistula (EA/TEF) remains one of the most frequently missed congenital anomalies prenatally. The aim of our study was to elucidate the sonographic manifestation of EA/TEF throughout pregnancy. Methods: This was a retrospective study of data obtained from a tertiary center over a 12‐year period. The prenatal ultrasound scans of fetuses with EA/TEF were assessed to determine the presence and timing of detection of three principal signs: small/absent stomach and worsening polyhydramnios, both of which were considered as 'suspected' EA/TEF, and esophageal pouch, which was considered as 'detected' EA/TEF. We assessed the yield of the early (14–16 weeks' gestation), routine mid‐trimester (19–26 weeks) and third‐trimester (≥ 27 weeks) anomaly scans in the prenatal diagnosis of EA/TEF. Results: Seventy‐five cases of EA/TEF with available ultrasound images were included in the study. A small/absent stomach was detected on the early anomaly scan in 3.6% of fetuses scanned, without a definitive diagnosis. On the mid‐trimester scan, 19.4% of scanned cases were suspected and 4.3% were detected. On the third‐trimester anomaly scan, 43.9% of scanned cases were suspected and 33.9% were detected. An additional case with an esophageal pouch was detected on magnetic resonance imaging (MRI) in the mid‐trimester and a further two were detected on MRI in the third trimester. In total, 44.0% of cases of EA/TEF in our cohort were suspected, 33.3% were detected and 10.7% were suspected but, eventually, not detected prenatally. Conclusions: Prenatal diagnosis of EA/TEF on ultrasound is not feasible before the late second trimester. A small/absent stomach may be visualized as early as 15 weeks' gestation. Polyhydramnios does not develop before the mid‐trimester. An esophageal pouch can be detected as early as 22 weeks on a targeted scan in suspected cases. The detection rates of all three signs increase with advancing pregnancy, peaking in the third trimester. The early and mid‐trimester anomaly scans perform poorly as a screening and diagnostic test for EA/TEF. © 2020 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : A video abstract of this article is available online here .